Polyploidy but Not Range Size Is Associated With Seed and Seedling Traits That Affect Performance of Pomaderris Species - Chan, Jason C. S.; Ooi, Mark K. J.; Guja, Lydia K. (Frontiers in Plant Science, 2022)
Ploidy and species range size or threat status have been linked to variation in phenotypic and phenological seed and seedling traits, including seed size, germination rate (speed) and seedling stature. There is surprisingly little known about the ecological outcomes of relationships between ploidy, key plant traits, and the drivers of range size. Here we determined whether ploidy and range size in Pomaderris, a genus of shrubs that includes many threatened species, are associated with variation in seed and seedling traits that might limit the regeneration performance of obligate seeders in fire-prone systems. We experimentally quantified seed dormancy and germination processes using fire-related heat treatments, and evaluated seedling performance under drought stress. We also examined the association of seed size with the other seed and seedling traits. Polyploids had bigger seeds, a faster germination rate, and larger and taller seedlings than diploids. There was a lack of any clear relationship between range size and seed or seedling traits. The ploidy effects observed for many traits are likely to be indirect and associated with the underlying seed size differences. These findings indicate that there is a higher potential competitive advantage in polyploid than diploid Pomaderris during regeneration, a critical stage in the post-fire environment. This insight to the regeneration phase may need to be considered when planning and prioritizing management of threatened species.